Survival of adults with primary malignant brain tumours in Europe; Results of the EUROCARE-5 study. Issue 15 (October 2015) - ,; Hackl, M.; Zielonke, N.; Oberaigner, W.; Van Eycken, E.; Henau, K.; Valerianova, Z.; Dimitrova, N.; Sekerija, M.; Zvolský, M.; Dušek, L.; Storm, H.; et al.
Abstract: Background: Primary malignant brain tumours are rare but represent a serious health burden due to their poor survival. This manuscript describes the survival of malignant brain tumours in adults diagnosed 2000–2007 in Europe. Methods: For this study we analysed patients archived in 86 European population-based cancer registries, followed up to 31st December 2008. Only primary malignant neuroepithelial brain tumours (with pathological confirmation) and primary malignant unspecified brain tumours without pathological confirmation were included. We estimated 1-year and 5-year relative survival (RS) weighted by age group and country. We also estimated country-specific and age-specific survival, together with survival differences between time periods (for 1999–2001, 2002–2004 and 2005–2007). Results: Glioblastoma represents 49% of all brain tumours, followed by other/unspecified astrocytoma (18%), oligodendroglioma/oligoastrocytoma (9%), ependymoma (1.5%) and embryonal tumours (1%). Five-year RS was 20% for all tumours combined, but ranged from 58% for ependymoma to only 6% for glioblastoma and sharply decreased with increasing age. Differences between countries were relatively small, but generally RS in Ireland/United Kingdom (UK) and Eastern Europe was below the average. An increase in 1-year RS (up to 10–12%) was noted over time, being largest in Central and Northern Europe in patients between 45 and 74 years of age. Conclusions: Despite an increase in 1-year RS in most European regions, the survival of primary malignant brain tumours is still poor. Disparities between countries were evident, being even larger at the end of the study period than at the beginning, suggesting differences in availability of the latest treatment modalities.